Helping Children with Homework: FAR1718/FM445, 3/2012 - Liss Radunovich, Heidi (EDIS, 2012)
“Although children and their parents often dread homework, it provides an important opportunity for children to practice what they have learned in school, get more in-depth information, apply skills learned more broadly, obtain important learning and organizational skills, and learn how to work independently with self-discipline. Homework can also give parents a sense of what their children are doing in school and how well they are doing. And homework can even enhance parents’ relationships with their children.” This 2-page Family Album Radio transcript was written by Heidi Liss Radunovich, and published by the UF Department of Family, Youth and Community Sciences, March 2012.